2019
DOI: 10.1021/acs.nanolett.9b04124
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Functionalization-Controlled Activity of Metal–Organic Framework-Encapsulated Pt Nanocatalyst toward Activation of Water

Abstract: We first report the systematic control of the reactivity of H2O vapor in metal–organic frameworks (MOFs) with Pt nanocrystals (NCs) through ligand functionalization. We successfully synthesized Pt NCs covered with a water-stable MOF, UiO-66 (Pt@UiO-66), having different metal ions or functionalized ligands. The ligand functionalization of UiO-66 significantly affected the catalytic performance of the water–gas shift reaction, and the replacement of Zr4+ ions with Hf4+ ions in UiO-66 had no impact on the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 63 publications
0
24
0
2
Order By: Relevance
“…Finally, in selecting papers for highlighting we have necessarily omitted other clearly relevant papers, including papers by groups led by Rahul Banerjee, 425 Silvia Bordiga, 426 Avelino Corma, [427][428][429][430][431] Deanna M. D'Alessandro, 432 Zhengping Dong, 433 Mohamed Eddaoudi, 434 Roland A. Fischer, 277,435,436 Jorge Gascon, [437][438][439] Stefan Kaskel, 440,441 Hiroshi Kitagawa, 442,443 Susumu Kitagawa, 444 Jing Li, 445 Yangyang Liu, 446,447 Tian-fu Liu, 448 Jeffery Long, 449 Connie C. Lu, 450 Amanda J. Morris, 451 Ali Morsali, 254,452,453 Unni Olsbye, 454 W. L. Queen, 455 Matthew Rosseinsky, 456 Natalia B. Shustova, 457 Berend Smit, 458,459 Norbert Stock, [460][461][462][463] Shane G. Telfer, [464][465][466] Fernando Uribe-Romo, 467 Jenny G. Vitillo,…”
Section: Access To Unprecedented Catalysis Mechanisms Via Unprecedented Active-site Coordinationmentioning
confidence: 99%
“…Finally, in selecting papers for highlighting we have necessarily omitted other clearly relevant papers, including papers by groups led by Rahul Banerjee, 425 Silvia Bordiga, 426 Avelino Corma, [427][428][429][430][431] Deanna M. D'Alessandro, 432 Zhengping Dong, 433 Mohamed Eddaoudi, 434 Roland A. Fischer, 277,435,436 Jorge Gascon, [437][438][439] Stefan Kaskel, 440,441 Hiroshi Kitagawa, 442,443 Susumu Kitagawa, 444 Jing Li, 445 Yangyang Liu, 446,447 Tian-fu Liu, 448 Jeffery Long, 449 Connie C. Lu, 450 Amanda J. Morris, 451 Ali Morsali, 254,452,453 Unni Olsbye, 454 W. L. Queen, 455 Matthew Rosseinsky, 456 Natalia B. Shustova, 457 Berend Smit, 458,459 Norbert Stock, [460][461][462][463] Shane G. Telfer, [464][465][466] Fernando Uribe-Romo, 467 Jenny G. Vitillo,…”
Section: Access To Unprecedented Catalysis Mechanisms Via Unprecedented Active-site Coordinationmentioning
confidence: 99%
“…[35,58,73,74] Moreover, the tailorable/ functionalizable porosity of MOF endows the designed composites with tunable sorption selectivity and stability, which are key factors for catalysis. [59,75,76] In the following section, we will discuss the advances of core-shell MOF-based composites in selective, efficient energy-related catalytic reactions.…”
Section: Core-shell Composites For Catalysismentioning
confidence: 99%
“…This revealed that apart from the core-shell encapsulation, the direct MOF functionalization is a convenient strategy to improve the catalytic properties. [75] Figure 14. A) Pt@UiO-66-H. B) Pt@UiO-66-H(Hf).…”
Section: H 2 Productionmentioning
confidence: 99%
“…For example, NH 2 groups added to the BDC linkers of UiO-66 increase the catalytic activity of the MOF for the hydrolysis of warfare agent simulants. 51 , 52 …”
Section: Surface Chemistry Of Mof Metal Oxide Cluster Nodesmentioning
confidence: 99%